Immunological Emergency in Neonate: Case Report and Role of Early Screening - Samedi, Veronica Mugarab; Shafey, Amy; Al Awad, Essa; Favela, Luis Murguia (American Journal of Perinatology Reports, 2018)
Healthy looking newborns may have severe combined immunodeficiency (SCID), and neonatologists frequently are the first physicians to encounter these patients. Physicians usually have a high index of suspicion for this condition in presence of certain risk factors (unexplained infants' deaths, consanguinity); however, >80% of infants with SCID have no positive family history. A timely diagnosis of this condition is crucial in decreasing both mortality and morbidity. The only way to detect SCID prior to the onset of infections is newborn screening (NBS). In term infants, NBS has 99.99% sensitivity for SCID, with no false negatives. In preterm infants, screening is less accurate due to a lack of standard T cell receptor excision circle (TREC) values in this age group. We report a case of SCID in term infants born to consanguineous parents who were presented with clinical and laboratory findings of erythroderma, severe infection, failure to thrive, eosinophilia, and elevated immunoglobulin E (IgE) together with immunodeficiency. A timely diagnosis was followed by successful hematopoietic stem cell transplantation (HSCT) therapy.
Keywords: neonate; immunodeficiency; screening; SCID; stem cells; TREC